A DFT study of dodecahedral beryllium silicide cage clusters - Fioressi, Silvina Ethel (2012)
Density functional theory calculations have been conducted on 20- and 32-atom dodecahedral and facecapped dodecahedral cage clusters of beryllium and silicon. Stable Be24Si8, Be12Si8 and Be12Si20 cages are described, as is a stuffed cluster consisting of dodecahedral Si20 with an endohedral icosahedral Be12. Especial stability is associated with clusters in which faces are capped by silicon atoms, acting as electron donors to beryllium atoms.